The symbolic meaning of the tunis motif of the tanimbar weaving at aesthetic value,applied to clothing in learning fashion design at ciputra university - Soelistyowati, Soelistyowati; Rahadiyanti, Melania (Jurnal Konseling dan Pendidikan, 2025)
Tanimbar weaving, especially the Tunis motif, is one of Indonesia's cultural riches that is rich in historical, philosophical, and aesthetic values. This study explores the symbolic meaning of the Tunis motif in relation to aesthetic values ​​and its application in fashion design at the Fashion Design Department at Ciputra University Surabaya. The Tunis motif, which originates from the Tanimbar Islands, has a deep cultural meaning, representing strength, direction, and protection. This motif is inspired by traditional hunting tools, bows and arrows, which symbolize the readiness and alertness of the Tanimbar people. This study uses Charles Pierce Sander's Triadic Interplay theory, which divides signs into three categories: Representamen (sign), Object (sign reference), and Interpretant (understanding). Through this approach, this study reveals how the Tunis motif functions more than just a decorative element, which acts as a medium for cultural expression and identity. This study applies the Tunis motif in modern fashion design, examining how this motif enhances aesthetic value while preserving cultural heritage. The integration of motifs into contemporary clothing designs not only enriches fashion, but also strengthens the cultural identity of the Tanimbar people. This study highlights the importance of cultural preservation through fashion design innovation and the role of local artisans in the global creative economy. The application of motifs in fashion also supports economic empowerment and sustainability in the creative industry, with potential benefits for the local economy.